PROFITABILITY OF CAPM MOMENTUM STRATEGIES IN THE US STOCK MARKET - Chong, Terence Tai-Leung; He, Qing; Ip, Hugo Tak-Sang; Siu, Jonathan T. (International Journal of Business and Society, 2017)
This paper provides a historical review of the performance of the risk-adjusted momentum strategies when buying and selling stocks according to the alpha estimates of the CAPM and Fama–French regressions. Our sample covers over 60 million US daily firm-return observations. High Sharpe ratios are obtained under our risk-adjusted strategies. It is also found that stock market crashes have no apparent impact on our momentum profits. Keywords: Momentum Strategies; Sharpe Ratio; Fama-French Model; CAPM Model.